Фізико-хімічні та технологічні засади підвищення ефективності використання негашеного вапна у композиційних вʼяжучих системах. - Якименко, Ярослав Богданович (Національний університет "Львівська політехніка", 2013)
Дисертація присвячена питанням розроблення теоретичних основ одержання композиційних в’яжучих систем з підвищеним вмістом негашеного вапна шляхом направленого керування процесами гідратаційного тверднення за рахунок використання хімічних добавок та технологічних підходів, що забезпечують необхідні експлуатаційні властивості в’яжучих різноманітного призначення. Встановлено умови реалізації потенційних в’яжучих властивостей кальцію оксиду при гідратаційному твердненні за рахунок встановлення закономірностей формування структури портландитового каменю. Визначено особливості формування фазового складу і мікроструктури композиційних в’яжучих систем, а також досліджено їх будівельно-технічні властивості. Показано можливість використання підвищеної кількості модифікованого негашеного вапна у складі неавтоклавного контруктивного та теплоізоляційного газобетонів. Розроблено технологічні параметри одержання розширних та напружувальних цементів. Здійснено промислову апробацію розроблених композиційних в’яжучих систем. Диссертация посвящена вопросам разработки теоретичеких основ получения композиционных вяжущих системм с повышенным содержанием негашеной извести путем направленного управления процессами гидратационного твердения при использовании химических добавок и технологических приёмов, которые обеспечивают необходимые эксплуатационные свойства вяжущих широкого спектра назначения. Определены условия реализации потенциальных вяжущих свойств кальция оксида при его гидратационном твердении за счет изучения закономерностей формирования структуры портландитового камня. Установлены особенности образования фазового состава и микроструктуры композиционных вяжущих, а также исследованы их физико-механические и строительно-технические свойства. Показана возможность использования повышенного колличества модифицированной негашеной извести в составе неавтоклавного конструктивного и теплоизоляционного газобетонов. Разработаны технологические параметры получения расширяющихся и напрягающих цементов и наведены результаты производственных испытаний. The work deals with the research results concerning the development of theoretical principles and technology of composite binders with a high content of quicklime via solidification process directional control by chemical additives as well as technological methods ensuring the required operational properties of a wide range purposes binding materials. On the basis of physicochemical analysis of hydration parameters of alkaline earth metals oxides, it was found that hydration activity of these oxides is strongly affected by the production background and self-dispersion effect under high pressure steam. The kinetic parameters of calcium oxide hydration in water and electrolyte solutions were investigated. It is shown that, depending on the conditions, hydration of CaO can occur in accordance with a soluble or topochemical schemes. The formation of portland frame during lime hydration hardening can occur only in the presence of soluble phase, and formation of portland in the solid phase is accompanied by the system expansion and creation of expansion pressure. The classification of alkali and alkali-earth metal salts additives that change CaO hydration activity was developed. The induction period was found to be an important characteristic of monomineral binding materials that causes the required rheological properties of solutions based on them. Using chemical additives it is possible to create conditions for the induction period and hydration hardening of calcium oxide.It was found that the morphology and habit of portland crystals have a key effect on the physical and mechanical properties of lime stone. The influence of the SO42- and BO45- anions on the peculiarities of portland crystals formation and mechanism of their retard action during CaO hydration were investigated. The conditions for full realization of potential binding properties of calcium oxide during its hydration hardening were identified by establishing general regularities of portland stone structure in hydraulic binders. The optimum compositions, containing quicklime, hydraulically active and sulphate containing components were developed. The basic dependencies of phase composition and microstructure of composite binders were identified, and their physical, mechanical and building-technical properties were investigated. It is shown that the formation of lamellar habit Са(ОН)2 crystals with high specific surface area increases the contact area with the pozzolanic particles, which also intensifies the formation of hydrosilicates with variable composition. The lime-gypsum binders with high content of CaO, characterized by high early strength and water resistance were developed. While adding boric acid to the lime-gypsum compositions the increase in the strength and water resistance factor was observed. It is grounded that modified quicklime may be used in the increased amount in the non-steam-cured structural aerated concrete and insulation. The complex additive consisting of quick lime and colloidal gypsum reduces shrinkage deformation in such concrete by 2.0-2.5 times. The increased hydration activity of phosphoanhydride binder was observed associated with crystal characteristics of anhydrite, obtained during burning at 900° C with the addition of lime. The construction and technical properties of phosphoanhydride binder and its structure formation were investigated. The results of commercial tests of binding compositions containing quicklime in non-steam-cured concrete, strength and expanding cements are presented.
Физико-химические и технологические основы повышение эффективности использования негашеной извести в композиционных вяжущих системах
Physico-chemical and technological principles of raising the efficiency of quicklime used in the composite binding systems
Keywords: негашене вапно; портландит; гідратаційне тверднення; вапняновмісні гідравлічні в’яжучі; фосфоангідритові в’яжучі; напружувальні та розширні цементи; негашеная известь; портландит; гидратационное твердение; известковосодержащие гидравлические вяжущие; фосфоангидритовые вяжущие; напрягающие и расширяющиеся цементы; quicklime; portlandite; hydration hardening; lime-containing hydraulic binders; phosphoanhydride binders; strength and expanding cements